THE ADVANCED TACTICS OF THE MANAGEMENT OF PATIENTS WITH VENOUS THROMBOEMBOLISM: THE ROLE OF RIVAROXABAN AT VARIOUS STAGES OF TREATMENT - S. R. Gilyarevskiy (Рациональная фармакотерапия в кардиологии)
Venous thromboembolism (VTE) is one of the most common cardiovascular disease, and can lead to death or the development of complications and disability. Modern approaches to the determination of the treatment strategy in patients with VTE are considered. The role of thrombolytic therapy is highlighted, as well as the choice of anticoagulants, including new oral anticoagulants (NOAC). EINSTEIN-PE is the only, specially planned and performed study of the NOAC in patients with pulmonary embolism that confirmed the validity of monotherapy tactics with rivaroxaban in patients with VTE. The results of this study are considered in detail.